Functional and Structural Investigation of Chalcone Synthases Based on Integrated Metabolomics and Transcriptome Analysis on Flavonoids and Anthocyanins Biosynthesis of the Fern Cyclosorus parasiticus - Niu, Meng; Fu, Jie; Ni, Rong; Xiong, Rui-Lin; Zhu, Ting-Ting; Lou, Hong-Xiang; Zhang, Peng; Li, Jianxu; Cheng, Ai-Xia (Frontiers in Plant Science, 2021)
The biosynthesis of flavonoids and anthocyanidins has been exclusively investigated in angiosperms but largely unknown in ferns. This study integrated metabolomics and transcriptome to analyze the fronds from different development stages (S1 without spores and S2 with brown spores) of Cyclosorus parasiticus. 221 flavonoid and anthocyanin metabolites were identified between S1 and S2. Transcriptome analysis revealed several genes encoding the key enzymes involved in the biosynthesis of flavonoids and anthocyanins were upregulated in S2, which were validated by qRT-PCR. Functional characterization of two chalcone synthases (CpCHS1 and CpCHS2) indicated that CpCHS1 can catalyze the formation of pinocembrin, naringenin and eriodictyol respectively, however, CpCHS2 was inactive. The crystallization investigation of CpCHS1 indicated that it has a highly similar conformation and share a similar general catalytic mechanism to other plants CHSs. And by site-directed mutagenesis we found seven residues especially Leu199 and Thr203 are critical to the catalytic activity for CpCHS1.